The epidemiology of schizophrenia - Murray, Robin M., 1944- (Cambridge University Press, 2003)
The first comprehensive, epidemiological overview of schizophrenia, drawing together the findings from social, genetic, developmental and classical epidemiology. Controversial issues on its nature and cause are explored in depth, and separate chapters are devoted to suicide, violence and substance abuse, new prospects for treatment, and prevention.
Keywords: Schizophrenia -- Epidemiology.; Schizophrenia -- epidemiology; Schizophrenia -- etiology; Risk Factors; Schizophrénie -- Épidémiologie.; PSYCHOLOGY -- Mental Health.; PSYCHOLOGY -- Mental Illness.; MEDICAL -- Mental Health.